LEGAL VACUUM IN INTERFAITH MARRIAGE RULES IN INDONESIA - Sidiqah, Meliyani (IBLAM LAW REVIEW, 2023)
The legal vacuum regarding the rules of interfaith marriage was not something new. However, this matter has not been resolved by the Government of Indonesia. After the Marriage Law’s promulgation, the rules of interfaith marriages "disappeared", even though before the promulgation of the Marriage Law, interfaith marriages were regulated clearly and firmly. The phenomenon of interfaith marriage in society which was very difficult to avoid was an essential point of concern for the state to accommodate the rules regarding interfaith marriages. This article discussed the phenomenon of interfaith marriages in Indonesia and the legal rules of interfaith marriages before and after the promulgation of the Marriage Law. This article was the result of normative juridical research using the statutory approach method. The data used was secondary data consisting of primary legal materials, secondary legal materials, and secondary legal materials, which were collected from the literature and then analysed using qualitative analysis methods. Based on the research results, many Indonesian people still carry out interfaith marriages in Indonesia, and the rules of interfaith marriages formulated in the Marriage Law are inadequate. The Indonesian government must accommodate interfaith marriage arrangements in order to provide legal certainty to all people.